Hydrated Lime Effects on Geotechnical Properties of Clayey Soil (Journal of Engineering, 2020)
Cohesive soils present difficulties in construction projects because it usually contains expansive clay minerals. However, the engineering properties of cohesive soils can be stabilized by using various techniques. The research aims to elaborate on the influences of using hydrated lime on the consistency, compaction, and shear strength properties of clayey soil samples from Sulaimnai city, northern Iraq. The proportions of added hydrated lime are 0%, 2.5%, 5%, 7.5% and 10% to the natural soil sample. The results yielded considerable effects of hydrated lime on the engineering properties of the treated soil sample and enhancement its strength. The soil's liquid limit, plasticity index, and optimum moisture content were decreased with the increase of hydrated lime percent. The soil's other geotechnical properties such as plastic limit, maximum dry density, and unconfined compressive strength were increased with the hydrated lime content increase. The oedometer test results produced a notable decrease in the compressibility characteristics of the lime-treated soil sample. Hence, hydrated lime is successfully contributed and can be considered as an effective material to improve the strength, compressibility, and consistency properties of the cohesive soils in Sulaimani city.